The effect of psychological comfort on the interior design of patient rooms in private hospitals Al-Razi Hospital and Al-Mahayni Hospital in Damascus as a model"" (Damascus University Journal for engineering sciences, 2024)
The research aims to study the elements of interior design, and their role in raising the efficiency of patients’ accommodation rooms, and employing these elements to integrate with the therapeutic contexts in achieving recovery, and in line with the psychological comfort of patients in hospitals in general, and private hospitals in particular, as they depend on contemporary trends in the interior design of hospitals The special focus on linking the therapeutic environment, by introducing the psychological dimension in the treatment process, and the efficiency of the elements of the internal environment that directly affect the psychological comfort of patients.The research relied on the descriptive analytical method, due to its relevance with the nature of the research using the quantitative scale. The questionnaire was used in analyzing the results, which contained vocabulary for psychological comfort (privacy, external views, comfort and control, internal appearance, family support, and furniture);Among the most important findings of the research is the existence of a soft positive relationship between the interior design elements and the psychological comfort of patients in the residence rooms with the possibility of providing a supportive environment for psychological comfort, and the existence of a negative correlation between the personal information of patients (age, educational attainment, duration of stay) and psychological comfort in Patients' accommodation rooms in private hospitals.
Keywords: psychological comfort; interior design; interior design elements; private hospitals